Przydatność ekonomicznej wartości dodanej w zarządzaniu wartością przedsiębiorstwa - Nita, Bartłomiej (Usefulness of Economic Value Added in Value-Based Management, 2005)
The paper presents the conception of Economic Value Added in the context of Value-Based Management. Some remarks concerning the historical sources of this metric are also described. The main emphasis is put on showing the advantages and disadvantages of using Economic Value Added in a corporate from the point of view of performance evaluation and its correlation with the total return to shareholders. Another issue addressed is EVA as the basis of an incentive compensation plan that encourages managers to think and act like owners. Some results of empirical research and analysis, where usefulness of Economic Value Added is considered to be questionable, are also quoted in the article.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 289-298